Ancient Christian Martyrdom: Diverse Practices, Theologies, and Traditions. By Candida R. Moss - Kao, Fiona (The journal of theological studies, 2014)
Candida Moss states that the purpose of this book is to reveal how martyrs were created and for what purposes, the ideologies of martyrdom, and how ideological power was utilized. In it, she challenges several scholarly assumptions: that there was a singular ideology of martyrdom (she claims there were several); that the Romans persecuted the Christians (there is little evidence from the Roman side); that the relationship between the New Testament and martyrdom literature was a linear development (the two influenced each other); and that apologetic texts, apocryphal acts of the apostles, and martyr acts were widely different.